Effects of berbamine on intracellular calcium concentration in cultured HeLa cells. - Li Bai-yan; Fu Bing; Zhao Yan-ling; Li Wen-han (Acta Pharmacologica Sinica, 2016)
AIM: To study the involvement of Ca2+ signaling and the effects of berbamine (Ber) on intracellular calcium concentration ([Ca2+]i) elevated in cultured HeLa cells. METHODS: [Ca2+]i was measured by confocal microscopy in single HeLa cell loaded with Fluo 3-AM. The change of [Ca2+]i was represented by fluorescent intensity (FI). RESULTS: (1) In the presence of extracellular Ca2+ 1.3 mmol.L-1, the resting level of FI was 186 +/- 44, n = 49 cells from all control experiments, and KCl, NE, caffeine, and calcimycin (Cal) all induced [Ca2+]i elevations in cultured HeLa cells. (2) The resting level of FI was not affected by pretreatment with Ber. The FI increased by KCl 60 mmol.L-1, NE 100 micromol.L-1, and Cal 30 micromol.L-1 were attenuated (P < 0.05 or P < 0.01), the slope and the time to peak of FI increase were decreased and prolonged. (3) In the absence of extracellular Ca2+, caffeine 80 mmol.L-1-induced [Ca2+]i mobilization was not inhibited by Ber 100 micromol.L-1 pretreatment. (4) These effects of Ber were similar to those of verapamil (Ver) 10 mumol.L-1. CONCLUSION: Although it was derived from cervical cancer, the HeLa cells which were belong to the nonexcitable cell possessed the similar biological properties with excitable cells, and Ca2+ also played a crucial role in signal transduction processes.